Sustainable synthesis of bakuchiol-mediated gold nanoparticles for drug delivery against bacterial strains and tumor microenvironments, and its in silico target proteins identification - Mishra, Pooja; Faruqui, Tabrez; Khanam, Sheeba; Khubaib, Mohd; Ahmad, Irfan; Saeed, Mohd; Khan, Salman (Frontiers in Molecular Biosciences, 2024)
The sustained synthesis of gold nanoparticles (GNPs) is gaining attention for biomedical applications. This study evaluated the antibacterial and anticancer potential of bakuchiolmediated gold nanoparticles (Bak-GNPs) through network analysis, molecular docking, and Page 2 of 25 green synthesis. Network analysis and molecular docking identified GNAI3 as the most effective protein target for bakuchiol in lung cancer, with a binding energy of -7.5 kcal/mol compared to PTGER3's -6.9 kcal/mol. Bak-GNPs were synthesized using bakuchiol, which is a phytocompound with antioxidant and therapeutic properties. TEM analysis confirmed spherical Bak-GNPs with an average size of ~ 15 nm. FTIR spectra indicated functional groups in bakuchiol likely responsible for nanoparticle capping. Bak-GNPs exhibited potent antibacterial activity against Gram-positive and Gram-negative bacteria, confirmed by MIC values, and significant anticancer effects on A549 and HepG2 cells, with IC50 values of 11.19 µg/mL and 6.6 µg/mL, respectively. Bak-GNPs induce apoptosis and inhibit the proliferation of lung and liver tumor microenvironments by increasing ROS production. Exposure to Bak-GNPs at the IC50 for 24 h significantly reduced cell proliferation in both cell lines. This study highlights the promising antibacterial and anticancer properties of bakuchiol-mediated GNPs for biomedical applications. This green synthesis approach using bakuchiol provides a sustainable method for producing nanoparticles with enhanced biological activities. Further exploration of the pharmacological properties and mechanisms of Bak-GNPs is required to optimize their therapeutic efficacy for clinical use.